Between bonuses and minimum wages from tumble to tumble, a policy without direction? - Acosta, Alberto (2020)
Lowering wages is not a remedy for depression, because capitalists do not immediately devote the profits derived from it to the purchase of investment goods "Michal Kalecki "The economy is not free of values ​​and economists must be transparent about the value judgments they make. This applies especially to those value judgments that may not be visible to the untrained eye" Thesis 3 of the 33 theses for a reform of the economy The economy is a part of human knowledge that is still in its infancy and is even caught between mazes and reformulations. That is why it is common to find various dogmas within it. An example is the "orthodox, conservative and prudent: OCP" argument that increasing pensions and minimum wages reduces or deteriorates employment; Or, in other words, reducing labor costs creates more jobs and improves competitiveness. For the defenders of this OCP vision, pensions and minimum wages "block" the "optimizing" trend of the free market, so that their increase would create "non-optimal" conditions of higher unemployment or worse working conditions. In addition, higher pensions would widen the fiscal deficit, creating greater economic distortions, say the OCP economists.